Edukasi Pencegahan Rabies Bagi Siswa Sekolah Dasar - Honey Ndoen; Agustinus Ole; Antonia Gale; Erinda Ndjurumbah; Fransiska Mongko; Juanito Nesimnasi; Stefania Bere; Trivonia Wula (GOTAVA, 2024)
Rabies is a zoonotic disease caused by the rabies virus, which can be transmitted from animals to humans through bites or contact with the saliva of infected animals. The disease is acute and attacks the central nervous system, with a mortality rate of 100% if not treated properly. The educational activity conducted at SDN Oesapa Kecil 2, Kupang City, aimed to increase students' knowledge about rabies, including its definition, causes, modes of transmission, risk factors, and prevention measures. The targets of this activity were grade VI students of SDN Oesapa Kecil 2. The type of education conducted was interactive, involving students in discussions and question and answer sessions. The media used in this education included leaflets containing information about rabies. This activity used pre-test and post-test methods to measure changes in student knowledge before and after counseling. The results showed significant improvement, with the average pre-test score being 70 and post-test reaching 78.65. Before counseling, 55% of students were in the low knowledge category; after counseling, this number decreased to 30%.